2022
DOI: 10.1136/rmdopen-2021-002170
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol consumption and disease-specific outcomes in rheumatic and musculoskeletal diseases (RMDs): systematic reviews informing the 2021 EULAR recommendations for lifestyle improvements in people with RMDs

Abstract: BackgroundA EULAR taskforce was convened to develop recommendations for lifestyle behaviours in rheumatic and musculoskeletal diseases (RMDs). The aim of this paper was to review the literature on the relationship between smoking and alcohol consumption with regard to RMD-specific outcomes.MethodsTwo systematic reviews were conducted to identify systematic reviews and meta-analyses, published between 2013 and 2018, related to smoking and alcohol consumption in seven RMDs: osteoarthritis (OA), rheumatoid arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 97 publications
(102 reference statements)
1
27
0
1
Order By: Relevance
“…From March 2019 to May 2019, systematic reviews of original research were conducted, one for each of the six predefined exposures (excluding OA for certain exposures, as mentioned above) 18–21. Population, Intervention, Comparison, Outcome (PICO) strategies were written and search strategies were developed for each review.…”
Section: Methodsmentioning
confidence: 99%
“…From March 2019 to May 2019, systematic reviews of original research were conducted, one for each of the six predefined exposures (excluding OA for certain exposures, as mentioned above) 18–21. Population, Intervention, Comparison, Outcome (PICO) strategies were written and search strategies were developed for each review.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies found that cigarette smoking was associated with more SJC, TJC, higher VAS for pain and disease activity score [ 36 , 37 ], positivity of RF [ 37 , 38 ] and ACPA [ 38 ], more severe joint damage progression [ 37 , 39 ], and poorer response to first-line DMARDs [ 40 ]. But there were also contrary results from different cohorts [ 8 ]. In our study, smokers were characterized by a higher ESR and a higher positive rate of RF.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that cigarette smoking is associated with the prevalence of RA-ILD, combined pulmonary fibrosis and emphysema, rheumatoid nodules [ 1 ], and a poorer prognosis in both RA patients [ 8 ] and RA-ILD patients [ 9 , 10 ]. However, the impact of cigarette smoking on different patterns of lung involvements has not been studied in well-matched cohorts of RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review dealt with smoking and alcohol consumption in patients with rheumatic and musculoskeletal diseases (RMD), amongst others with gout. While tobacco use does not seem to have an influence on gout attacks or SUA, alcohol consumption showed a significant association between the number and type of alcoholic beverages and the occurrence of flares [ 37 ]; however, to account for cultural differences in this context studies focusing on ethnicity and geographical residence are still lacking but needed. Sugary soft drinks, fruit juices and high-fructose foods (fruit sugars) can increase SUA levels and should therefore be avoided.…”
Section: Resultsmentioning
confidence: 99%